INTERNATIONAL-LEGAL REGULATION AS A DETERMINANT FOR MEASURES AND PROCEDURES OF THE COMPETENT STATE AUTHORITIES TOWARDS DIPLOMATIC-CONSULAR REPRESENTATIVES - Marinković, Nemanja (NBP. Nauka, bezbednosti, policija, 2019)
In this paper, the rights and obligations of states under the Vienna Convention and diplomatic immunity are discussed, as well as that the state has to respect them and provide additional protection and assurance to the diplomats and their missions; the following heading states that diplomats, however, abuse this privileged position, including examples of how the most frequent abuses are committed, and that diplomats have a duty to obey the laws of the receiving state; and finally, dominantly, we discuss how the whole state can respond to the Convention and the laws through the diverse practice of the competent authorities, along with the examples. The methodological approach in this paper is based on the analysis of the content of documents, and the analysis of the content of scientific material (textbooks, monographs, studies, PhD and master’s theses, books of proceedings, journals, practicums).